Tualang honey supplementation attenuates the lipid profile In high cholesterol diet induced non-alcoholic steatohepatitis animal model - Alias, Mohd Afzal; Abdul Rahim, Roslina; Muhammad, Siti Aeshah @ Naznin; Abdullah, Nor Zamzila; A.Talib, Norlelawati (2021)
Introduction: Hypercholesterolaemia, insulin resistance and metabolic syndrome are the key features for Non-alcoholic Steatohepatitis (NASH) disease. Non pharmaceutical approaches, particularly nutritional counselling and diet prescription to reduce body weight remains the main recommendation for NASH management. Tualang honey (TH) has been proposed to improve lipid profiles and hence, may be beneficial in NASH management. Objectives: This study aimed to investigate the effects of TH at three different dosages on lipid profiles of rats given 12% high cholesterol diet (HCD). Methodology: Thirty male Sprague Dawley rats were fed with 12% HCD for 16 weeks. After 16 weeks, the rats were divided into four groups. The first group (Group A - control) was given distilled water while the rats in the remaining three groups, were treated with 1.2 g/kg (Group B), 2.4g/kg (Group C) and 3.0g/kg (Group D) doses of TH daily for four consecutive weeks. Rats in all groups were changed to a normal diet during this period. At the end of four weeks of TH treatment, blood samples were collected from the rats via the retro-orbital sinus and lipid profiles were analysed. Results: Compared to the control (Group A), the total cholesterol were reduced in all groups treated with TH (Group B, C and D); 1.84±0.134 vs. 1.52±0.192 vs. 1.62± 0.319 vs. 1.68±0.164 mmol/L respectively. The lowest triglycerides were seen in rats treated with 3.0 g/kg/day of TH; 1.26±0.487 vs. 1.18±0.414 vs. 1.34±0.622 vs. 0.98±0.356 mmol/L (Group A, B, C and D respectively). The LDL/HDL ratio was found to be the lowest in rats treated with 2.4 g/kg/day of TH (Group C). Conclusion: Supplementation of TH in addition to diet prescription may enhance the lipid profile modifications of HCD rats as compared to diet prescription alone, independent of TH dosage.